The Use of Coping Strategies for Everyday Challenges by University Students: Brazil‐Finland Cross‐National Study - dos Santos; Livia Oliveira; de Campos; Lucas Arrais; dos Santos, Adrielly; Peltomäki, Timo; Lantta, Tella; Varpula, Jaakko; Maroco, João; Campos; Juliana Alvares Duarte Bonini (Wiley-Blackwell, 2026)
The coping pattern of individuals who experience different cultures is influenced by different worldviews and ways of dealing with problems. This study aimed to estimate the psychometric properties of the BriefCOPE inventory and to compare coping strategies between Brazilian and Finnish university students. The study also aimed to identify how individual characteristics relate to coping strategies and explore the interconnections among strategies within the student samples from both countries. This is a cross-sectional observational study. Data was collected in Brazil using paper-and-pencil (n = 398, female = 66.6%; mean age = 21.0, SD = 2.2 years) and in Finland using an online survey (n = 165, female = 67.3% mean age = 26.9, SD = 7.2 years) during 2023 and 2024. A demographic questionnaire and the BriefCOPE Inventory were used. The fit of BriefCOPE to the samples was estimated using confirmatory factor analysis. Prevalences of coping strategies commonly used by students were calculated using a 95% confidence interval (95% CI). Multiple logistic regression models were developed, and the odds ratio (OR) was estimated considering each sample and its characteristics. Network analysis was carried out to identify the interconnection among coping strategies. The BriefCOPE Inventory presented adequate psychometric properties in both samples after refinement. Brazilian students showed a higher prevalence of using “Planning” and “Self-Distraction” strategies, while Finnish students showed a more uniform and balanced use of all coping strategies. In Brazil, students who reported having some type of mental health care had a greater probability of using adaptive strategies (“Active Coping”: OR = 3.51). In Finland, individual characteristics seem to have little effect on the choice of coping strategies. For both samples, “Planning” was the main strategy in maintaining networks. Finnish students have a larger and diverse repertoire to face everyday problems and better manage psychosocial demands compared to Brazilian students. Expanding students' coping repertoire can be important in preventing the development of symptoms associated with mental disorders in response to stress.